Concordance of Expert and Parental Opinion about Hypospadias Surgical Outcome Is Severity Dependent - Pérez-Brayfield, Marcos Raymond; Jorge, Juan Carlos; Avilés, Luis A.; Díaz, Joanne; Ortiz, Vanessa; Morales-Cosme, Wilfredo (Frontiers in Pediatrics, 2016)
Introduction. Hypospadias is a male congenital condition where the opening of the urethral meatus is not located in the typical anatomical position. It has been a challenge for empirical studies to ascertain the level of concordance of opinion among parents and urologists with regard to surgical outcomes according to hypospadias severity. Materials and Methods. Parents of children who had undergone hypospadias repair were recruited for this study (n=104). A set of questionnaires that included some items with Likert scale were created to evaluate postsurgical satisfaction by parents and urologists. SAHLSA-50, a validated instrument for adult Spanish-speaking adults, was used to assess health literacy. Cohen’s Kappa (k) coefficient was used to assess inter-observer agreement and Chi Square “Goodness of Fit” Test was used to determine probability of satisfaction. Findings. Concordance on the level of satisfaction with surgical outcomes for Type cases I was slight (k=0.20; CI 95% 0-0.60), for Type II cases was moderate (k= 0.54; CI 95% 0.13-0.94), and for Type III cases was substantial (k=0.62; CI 95% 0-0.56). However, the probability of satisfaction did not change according to severity (Chi Square “Goodness of Fit” Test; parents, p=0.84; pediatric urologists, p=0.92). These results cannot be explained by parental health literacy according to SAHLSA-50 test scores. Conclusions. The level of concordance of opinion among parents and urologists with regard to their level of satisfaction with surgical outcomes is related to hypospadias severity, whereby the greatest level of concordance of opinion was achieved among most severe cases. This study underscores the need for longer follow-up to properly assess satisfaction with hypospadias repair, especially for the less severe forms of the condition.